Description of a new species of Heligmonina Baylis, 1928 (Nematoda: Heligmonellidae) a parasite of Mastomys Natalensis (Rodentia: Muridae) from Swaziland and new data on the synlophe of Heligmonina Chabaudi (Desset, 1966) - Durette-Desset, Marie Claude (2007)
A new species of heligmosomoid nematode belonging to the subfamily Nippostrongylinae Durette-Desset, 1970 is described: Heligmonina wakelini n. sp., a parasite from the small intestine of the commensal rodent Mastomys natalensis (Smith, 1834) from Swaziland. It differs from the most closely related species H. boomkeri Durette-Desset & Digiani, 2005 by the number of the cuticular ridges in the female synlophe (10 vs 12), the width of the left ala, larger than the body diameter in the male, and the inclination of the axis of orientation of the ridges in both sexes (53° vs 70°). New morphological data (head and synlophe) on Heligmonina chabaudi (Desset, 1964), also a parasite of Mastomys natalensis in the Republic of Congo, are provided in order to compare with the new species.